2020
DOI: 10.34172/apb.2021.063
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant Production Using Mutant Strains of Pseudomonas aeruginosa and Bacillus subtilis from Agro-industrial Wastes

Abstract: Purpose: Biosurfactants are applied in drug formulations to improve drug solubility and in some cases, treat diseases. This study is focused on generating, extracting, purifying and then characterizing biosurfactants from bacterial isolates of palm oil wastes and abattoir soil origins. Methods: Eight (8) bacteria were isolated from the soil and sludge samples, out of which four (50 %) were found to produce biosurfactants. Bacillus subtilis (37.5 %) and Pseudomonas aeruginosa (50%) were isolated and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Strains with antibiotics are typical for rich soil samples. Pseudomonas sp., which are biosurfactant-producing bacterial strains [46], were also found. Pseudomonas play an important role in As biocirculation.…”
Section: Characteristics Of Soil and Tailing Microbial Communitymentioning
confidence: 86%
“…Strains with antibiotics are typical for rich soil samples. Pseudomonas sp., which are biosurfactant-producing bacterial strains [46], were also found. Pseudomonas play an important role in As biocirculation.…”
Section: Characteristics Of Soil and Tailing Microbial Communitymentioning
confidence: 86%
“…We adopted the method of Favaro et al (2016) as the standard for lipopeptide extraction. The bacteria that had grown on nutrient agar (nutrient agar: 20 g agar per litre of nutrient broth; nutrient broth: 3 g/L beef extract, 10 g/L peptone and 5 g/L NaCl; Adejumo et al, 2021) were transferred to 500 mL nutrient broth for subculturing by shaking in the dark at 28°C for 60 h. To extract the crude lipopeptide extract, the cultured cells were pelleted by centrifugation at 4°C, 1500 g for 20 min. The supernatant was acidified to pH 2 with 6 M hydrochloric acid, resulting in the precipitation of a white precipitate from the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…A significant number of currently available publications have demonstrated their efficacy in biosurfactant production and their role in successfully managing phytopathogens. [5,[117][118][119] Varnier et al, [120] concluded that Pseudomonas aeruginosa produced Rhamnolipid biosurfactants that improved grapevine immunity against Botrytis cinerea. In addition, using surfactants prevents the virus's spores from germinating and slows the growth of the mycelium they produce.…”
Section: Biosurfactants As Antimicrobial Against Plant Diseasesmentioning
confidence: 99%
“…The bacterial genera Pseudomonas and Bacillus are the ones that are utilized the most frequently in biosurfactant manufacturing. A significant number of currently available publications have demonstrated their efficacy in biosurfactant production and their role in successfully managing phytopathogens [5,117–119] . Varnier et al., [120] concluded that Pseudomonas aeruginosa produced Rhamnolipid biosurfactants that improved grapevine immunity against Botrytis cinerea .…”
Section: Application Of Biosurfactantmentioning
confidence: 99%